2023
DOI: 10.3390/agronomy13082187
|View full text |Cite
|
Sign up to set email alerts
|

Camelina sativa (L.) Crantz as a Promising Cover Crop Species with Allelopathic Potential

Martina Ghidoli,
Michele Pesenti,
Federico Colombo
et al.

Abstract: The ability of plants to release chemicals that affect the growth of other plants offers potential benefits for weed management and sustainable agriculture. This review explores the use of Camelina sativa as a promising cover crop with weed control potential. Camelina sativa, known for its high oil content and adaptability to diverse climatic conditions, exhibits allelopathic potential by releasing chemical compounds that inhibit weed growth. The crop’s vigorous growth and canopy architecture contribute to eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 132 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, camelina exhibits disease-suppressing properties, thanks to glucosinolates that exhibit fungicidal, nematocidal and bactericidal activities ( Arora and Kaushik, 2003 ). In fact, several studies have also indicated that camelina as a cover crop mitigates root diseases and improves the growth and yields of various crops, highlighting its potential as a sustainable and integrated pest management strategy in agriculture, making it emerge as a promising cover crop with weed control potential ( Acharya et al., 2020 ; Ghidoli et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, camelina exhibits disease-suppressing properties, thanks to glucosinolates that exhibit fungicidal, nematocidal and bactericidal activities ( Arora and Kaushik, 2003 ). In fact, several studies have also indicated that camelina as a cover crop mitigates root diseases and improves the growth and yields of various crops, highlighting its potential as a sustainable and integrated pest management strategy in agriculture, making it emerge as a promising cover crop with weed control potential ( Acharya et al., 2020 ; Ghidoli et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…A primary concern lies in the presence of glucosinolates (GLS), which represents a significant limitation for these applications. However, these molecules play a role in plant defense mechanisms, and, as noted by Ghidoli et al. (2023b) , their occurrence can be attributed to the allelopathic properties inherent in camelina ( Quéro et al., 2016 ; Hofmann et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations